(untitled) (Baghdad Science Journal, 2025)
this study was perform to defined the effect of fungus Metarhiziumanisopliae Sorokin with concentrations 5x101, 5x103 and 5x105 spore/ ml and Actelic insecticide with concentration 0.001% in in rate of germinate treated string bean seeds also study effect of packed bags in two different type: jute and polypropylene bags which treated with fungal suspension pervious mention and insecticide in rate infested the string bean seeds packed in it.Results of the study showed the following: Lower rate of weight loss of cowpea seeds appear in poly propylene bags 4.41, 5.95% after six months of treatment with 5x 105 spore/ ml and Actelic insecticide respectively compared with 15.08% to control treatment. The fungal concentrations and insecticide not effect Significantly in the rates of string bean germinate.